ANALYZING GRAMMATICAL ERRORS IN EFL STUDENTS' OPINION ESSAYS USING DEEPSEEK AI: PATTERNS AND PEDAGOGICAL IMPLICATIONS - Antara, I Made Agung Rai; Anggreni, Ni Putu Yunik (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2025)
This study aims to examine grammatical errors in opinion essays written by  Post-Intermediate Level students at the Bali International Language Centre (BILCEN) at Triatma Mulya University, utilising DeepSeek AI to discover error trends and offer strategic advice for educators. A qualitative analysis of 17 articles revealed 109 grammatical problems, predominantly characterised by article omission errors (42.2%), followed by subject-verb agreement (26.6%), preposition errors (17.4%), and tense inconsistencies (13.8%). The primary reasons for these errors encompass first-language interference and sentence fragmentation, indicative of the impact of Indonesian structures on English production. Examples include “work in a cruise ship” rather than “work on a cruise ship.” This study underscores the significance of a teaching methodology incorporating contrastive exercises, targeted feedback, and task design that balances fluency and accuracy. Strategic recommendations involve implementing exercises that juxtapose Indonesian and English structures and utilizing DeepSeek AI’s functionalities to provide comprehensive feedback. This study presents a novel approach for educators to tackle systematic grammatical issues in EFL students’ opinion writing. It underscores the potential of AI to enhance the precision of academic writing.